Establishing a Continuum of Acute Kidney Injury – Tracing AKI Using Data Source Linkage and Long-Term Follow-Up: Workgroup Statements from the 15th ADQI Consensus Conference. Issue 1 (26th February 2016) - Mehta, Ravindra; Bihorac, Azra; Selby, Nicholas M.; Quan, Hude; Goldstein, Stuart L.; Kellum, John A.; Ronco, Claudio; Bagshaw, Sean M.; ,
Background: Acute kidney injury (AKI) is independently associated with the development of chronic kidney disease, endstage kidney disease and increased all-cause and cardiovascular-specific mortality. The severity of the renal insult and the development of multiple AKI episodes increase the risk of occurrence of these outcomes. Despite these long-term effects, only a minority of patients receive nephrologist follow up after an episode of AKI; those that do may have improved outcomes. Furthermore, relatively simple quality improvement strategies have the potential to change this status quo. Methods: On this background, a working group of the 15 th Acute Dialysis Quality Initiative (ADQI) conference applied the consensus-building process informed by review of English language articles identified through PubMed search to address questions related to the opportunities, methodological requirements and barriers for longitudinal follow-up of patients with AKI in the era of electronic health records and Big Data. Results: Four consensus statements answering the key questions identified by the working group are developed. Conclusions: We have identified minimal data elements and potential data sources necessary to trace the natural history of patients from onset of AKI to long-term outcome. Minimum infrastructure and key barriers to achieving these goals are outlined together with proposed solutions.